Synthesis and Identification of Pb3TeO6 Compound - Мilyan P.М.; Kun, G.V.; Milyan Zh.І.; Molnar, J.I. (Physics and Chemistry of Solid State, 2015)
In present work, the physico-chemical analysis of the interaction process for PbO:TeO2=3:1 has been carried out. The ternary compound Pb3TeO6 was obtained by solid-phase reaction; this compound was identified by X-ray diffraction and chemical analysis.